The Statesman's yearbook 2016 the politics, cultures and economies of the world - Truner, Barry (Basingstoke Palgrave Macmillan, 2015)
Now in its 152nd edition, The Statesman's Yearbook continues to be the reference work of choice for accurate and reliable information on every country in the world. Covering political, economic, social and cultural aspects, the Yearbook is also available online for subscribing institutions: www.statesmansyearbook.com.
Time Zones Map Flags of the World/Map of the World (Colour Pull-out Section) Key World Facts Chronology of World Events PART I 1. International Organizations PART II: COUNTRIES OF THE WORLD A-Z: 2. Key Historical Events 3. Territory and Population 4. Social Statistics 5. Climate 6. Constitution and Government 7. Government Chronology 8. Recent Elections 9. Current Government 10. Current leaders 11. Defence 12. Economy 13. Energy and Natural Resources 14. Environment 15. Industry 16. International Trade 17. Communications 18. Social Institutions 19. Religion 20. Culture 21. Diplomatic Representatives 22. Further Reading Abbreviations Place and International Organizations Index Index of Current leaders
"Over 1,000 pages of essential facts. Just as current but more reliable than the internet, I consult it almost daily."-Professor R.N. Lebpw, King's College London.
Includes index.
Keywords: World politics -- 21st century; Economics -- History -- 21st century; Social indicators; Economic indicators